A systematic survey of 13 randomized trials of non-steroidal anti-inflammatory drugs for the prevention of heterotopic bone formation after major hip surgery. - Neal, B; Rodgers, A; Clark, T; Gray, H; Reid, I; Dunn, L; MacMahon, S (2000)
We performed a systematic survey of randomized trials to determine the effects of perioperative NSAIDs on the occurrence of heterotopic bone formation, gastrointestinal side-effects and long-term clinical outcomes after major hip surgery. 13 trials involving 4,129 individuals were identified. Overall, in 12 small trials of medium-to-high-dose regimens, there was a 57% reduction (95% confidence interval 51%-63%) in the risk of heterotopic bone formation. The results of one large trial of low-dose aspirin differed markedly (2% reduction (95% CI 12% reduction to 15% increase)). The NSAID regimens studied had no definite effect on gastrointestinal complications, and data about the effects of NSAIDs on pain and function were too few, and too incompletely reported, to draw conclusions about their effects on these outcomes. Routine prophylaxis against heterotopic bone formation with NSAIDs may be a useful adjuvant therapy for patients undergoing major hip surgery, but the overall balance of risks and benefits requires assessment in a large-scale randomized trial.